Concern with body form and nutritional evaluation in students of a private university - Teixeira, Patricia Angelica; Mello Locateni, Karyna Maria de; Silva, Wanderson Roberto da [UNESP] (Inst Brasileiro Pesquisa & Ensino Fisiologia Exercicio-ibpefex, 2018)
Introduction: Body image is an important concept that involves different aspects that can aid in the tracking of individuals with inappropriate behavior in front of the body. Objective: It was to identify the concern about the body shape of university students of a private institution and to relate it to the nutritional status, body fat percentage and sociodemographic variables. Methodology: 224 female students aged 21.8 +/- 3.8 years participated in the University Center of Patos de Minas - UNIPAM. The Body Shape Questionnaire (BSQ) was used to assess the concern about body shape. Analysis of Variance (ANOVA) compared the mean score of concern for body shape according to the study variables. Results: Most students presented low to moderate concern about body shape, which was significantly related to nutritional status, body fat percentage and students' economic class. Conclusion: University students classified as overweight / obese, with higher percentage of body fat and higher economic class presented higher scores of concern with body shape. These variables may be important in the elaboration of research and/or clinical protocols that seek to evaluate aspects of body image in university students.
Keywords: Body shape; Body image; Nutritional assessment; University students